The transformational crisis of globalization and the contingent trajectories towards innovative liberalism - Vlados, Charis Michael; Chatzinikolaou, Dimos (Frontiers in Political Science, 2025)
This integrative review examines the evolving landscape of globalization, aiming to understand the possible paths of the emerging global order. In a world marked by historical shifts, the research identifies three main paths: New Nation-Centric Fragmentation, New Multipolarity, and New Realistic and Innovative Global Liberalism. The last path looks most promising yet, regrettably, that prospect is fading as a driving force in today’s landscape—despite its promise of solid geopolitical stability, brisk economic growth, and vigorous technological progress. Recent global shifts, however, make such an outcome look increasingly remote.